Peran Lansia Sebagai Pemegang Otoritas Dalam Komunikasi Kesehatan Pencegahan Stunting - Monika Teguh; Rachmah Ida; Ratih Puspa; Burhan Bungin; Cosmas Gatot Haryono (Postgraduate, University of Mataram, 2023)
This research aims to know the roles of the elders as authority holders in the means of health communication for stunting prevention implemented in Trenggalek Regency, East Java. Stunting is the failure of growth and development caused by malnutrition at the first 1000 days of a child’s life. This problem can be prevented by providing nutrition needed by pregnant women and toddlers, but for preventing this the efforts of health communication are needed so that the mindset and behaviors of the society can change according to the health standards. Therefore, at Trenggalek Regency Kenek Beraksi program was implemented involving elders who may have authority to distribute knowledge and intervene behaviors which cause stunting to children. This research is qualitative research using case study method, by data gathering using in depth interview and document study. The result of this research shows that elders have significant roles in health communication for stunting prevention at Trenggalek Regency. Elders hold authorities because of the culture in society giving them privilege as respected and trusted figures. Furthermore, their knowledge and experience give them expert power and referent power making their family follow their guidance. In health communication, their health acts as a communicator delivering health messages. The effects felt from the elders’ involvement in this health communication program include the decrease of pregnant women having anemia, the increase of the toddlers’ nutritional adequacy achievement, and the increasing weights of toddlers, which altogether reduce the number of stunting at Trenggalek Regency